Comparing unimodal and bimodal countermovement jump force profiles in male collegiate athletes: a pilot study - Chen, M. Y.; Lee, H. J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The countermovement jump (CMJ) is commonly used to assess jumping ability in athletic testing batteries. The force-time (F-T) curve produced during a CMJ can reveal different jumping strategies employed by collegiate athletes. Some studies have found that a bimodal F-T curve may indicate inefficient use of the stretch-shortening cycle (SSC) in male rugby players, due to greater braking center of mass displacement. However, other research found the bimodal F-T curve was associate with a more effective CMJ compare to a unimodal curve, in both male and female collegiate students. The percent pre-stretch augmentation, calculated as the difference in jump height between CMJ and squat jump (SJ). Therefore, the aim of this pilot study was to compare unimodal and bimodal F-T curves in the CMJ and their relationship to elastic index (EI) in male collegiate athletes. METHODS: Ten male collegiate rugby sevens athletes performed 10-m sprint, SJ, and CMJ tests. Each test was performed twice. After testing, four separate case study comparisons were conducted by selecting athlete pairs who had similar heights and who consistently displayed either a unimodal (UNI) or one of three bimodal (BI) CMJ force-time (F-T) curves: bimodal with a higher first peak (BI-F), bimodal with a higher second peak (BI-S), or bimodal with equal peaks (BI-E). RESULTS: The unimodal (UNI) curve was associated with the lowest jump height, takeoff velocity, relative peak power, countermovement depth, and propulsion duration (30.61 cm, 2.49 m/s, 49.47 W/kg, 24.31 cm, and 212 ms, respectively). Additionally, the EI for UNI was -7%, indicating a lower CMJ height compared to squat jump (SJ) (32.74 vs. 30.61 cm). The bimodal curve with the second peak higher (BI-S) exhibited the lowest relative braking peak forces (22.49 N/kg). In contrast, the bimodal curve with the first peak higher (BI-F) showed the lowest relative propulsion peak forces (23.47 N/kg). The bimodal curve with equal peaks (BI-E) demonstrated the greatest jump height, takeoff velocity, relative peak power, and countermovement depth during CMJ (50.39 cm, 3.14 m/s, 68.85 W/kg, and 35.79 cm). However, BI-F had the largest EI, not BI-E (24% vs 10%). CONCLUSION: Assessing an athletes use of the SSC based solely on the CMJ force-time (F-T) curve may be insufficient. A more comprehensive evaluation examining individual test variables is necessary. We recommend practitioners compare variables such as the EI or SJ metrics. The unimodal or bimodal F-T curve exhibited during CMJ could be influenced by many factors including population demographics and training background. Rather than just the F-T curve, a multifaceted approach assessing SSC utilization through CMJ variables, SJ comparisons, and biomechanics is advised. Further research using electromyography and motion analysis to examine differences in muscle activity and kinetics between F-T curve types is suggested.